Promotion of professionalization through forming the scientific-educational environment at the university - I. V. Serafimovich; O. M. Кonkova (Открытое образование (Москва), 2017)
The article on the example of Yaroslavl branch of Plekhanov Russian University of Economics demonstrates the potential of the generated educational environment for the realization of the competence approach in training bachelors at enhancing the research activities of students. The aim of the study is to develop a cyclic model of promoting scientific research activities of students in specialized, interdisciplinary, university and interuniversity, regional and international projects. The aim of the study identified the following tasks: 1) to consider the peculiarities of the scientific-educational environment created in Yaroslavl branch and to allocate its structural elements which influence the formation and the development of students' professional competencies; 2) to analyze the technological aspects of the students' research activity organization at the university; to follow the process of the required competencies formation at the empirical level using the tools of scientific research; 3) to justify the various options implicitly contained in each method of organizing the students' research activity. The object of the study is the specific student group in the educational environment of the University. The study used different sociological methods such as including observation, unstructured interviewing, analysis of the students' reports about their research works. The article presents the results of the authors' applied research on the given problem and nearly 20 years of their practical experience in Yaroslavl branch of Plekhanov Russian University of Economics (former MESI). In the first part of the article the characteristic of the educational environment of the University from the point of view of its potential for forming and development of students' professional competences are considered, the place and the role of students' research work in the educational environment creation process are presented. The key problems that should be saluted to realize the full potential of the university educational environment are identified. The second part of the article focuses on the technological aspects of organizing students' scientific-research work at the university. The ways to enhance students' science activity in practical application are suggested. It is empirically proven that the involvement of students in scientific research provides their increasing interest to acquire professional competencies because they can see the good results of their efforts and feel the need in new achievements. The proposed materials contribute to the development of the theoretical foundations and the practical model of the students' research activity organizing as a necessary part of the university educational environment formation of which helps to achieve the university performance indicators, to carry on the mission of the university, to create conditions for implementing the academic values in general. The obtained results can be used by other institutions of higher education.